Model Blockchain Pada Rekam Medis Terdistribusi : Tinjauan Ontologi dan Epistemologi Terhadap Integritas Data - Sufa Atin; Hani Irmayanti; Andri Heryandi; Agus Nursikuwagus; Usep Mohamad Ishaq; Andrias Darmayadi (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2026)
Data integrity is a fundamental epistemological foundation for ensuring the validity and reliability of clinical knowledge. However, conventional Electronic Medical Record (EMR) systems still face structural and trust-related challenges due to centralized data management. This approach often leads to information fragmentation, limited interoperability among healthcare facilities, and low patient autonomy in controlling access to medical data. Philosophically, these conditions expose the limitations of an epistemology grounded in single authority, which is vulnerable to data manipulation, opacity, and centralized failures.This study examines, from a philosophical perspective, the role of distributed EMR systems based on permissioned blockchain—particularly Hyperledger Fabric—in strengthening guarantees of medical record data integrity. The research applies a philosophical conceptual analysis combined with a systematic literature review on EMR systems, blockchain technology, and data integrity. The analysis highlights the epistemological limitations of conventional EMRs, the defining features of permissioned blockchain architectures, and the ontological and epistemological implications of distributed consensus mechanisms. The findings indicate that, ontologically, blockchain redefines medical record data as distributed truth that is persistent and resistant to manipulation. Epistemologically, trust shifts from single authority to cryptographic validation and collective consensus, marking a paradigm shift in the legitimation of clinical knowledge in the digital era.